CROSS-SECTIONAL STUDY ABOUT KNOWLEDGE ON WARNING SIGNS AND RISK FACTORS OF COLON CANCER AMONG THE SUBURBAN POPULATION OF MALAYSIA - Karikalan, Barani; Selvanathan, Sakthi Shathi; May Hun, Tai; Kaur, Sangeeta (Malaysian Journal of Public Health Medicine, 2021)
Colorectal cancer (CRC) is the third most commonly diagnosed cancer worldwide. This study aimed to determine the knowledge level of CRC signs and risk factors among the multi-ethnic sub-urban population based on age, gender and education attainment levels. A cross-sectional study was carried out among residents of Kuala Selangor and Sabak Bernam from 28th January 2019 till 4th February 2019 by using a convenient sampling method. 350 participants were recruited and assessed using a validated and modified self-administered Cancer Awareness Measures (CAM) questionnaire which consists of sociodemographic characteristics, knowledge on warning signs and risk factors of CRC. Analysis was performed for symptoms and risk factors awareness against independent variables. The participants of the study are the semi-urban population of Malaysia and were able to recognise the CRC symptoms and risk factors, and exhibited an average overall CRC knowledge level. The analysis showed that the older age group (age > 50) participants were more familiar with the CRC symptoms and risk factors. Males have a greater percentage in the ‘High’ level of knowledge category compared to females although there was no significance between gender and knowledge level based on statistical analysis. Education attainment levels were found to be associated with the knowledge level whereby highly educated participants were more aware of the CRC symptoms and risk factors. Knowledge level on CRC symptoms and risk factors was average among the multi-ethnic sub-urban population. Therefore, health awareness programmes on CRC should be tailored to all especially the lower educational attainment groups, females and younger individuals in order to increase their awareness and reduce the CRC incidence.